Education Moderates the Association of Probable REM Sleep Behavior Disorder With Cognitive and Motor Impairments in Community-Dwelling Older People - Chen, Meijie; Chen, Jie; Xu, Xitong; Qiao, Fangwei; Wang, Xue; Ji, Shaozhen; Gu, Zhuqin; Chhetri, Jagadish K.; Chan, Piu (Frontiers in Neurology, 2020)
Abstract Objectives: To investigate the relationship between probable rapid eye movement (REM) sleep behavior disorder (pRBD) and cognitive/motor impairments in a community-dwelling population, and explore the moderating effects of education. Methods: In this cross-sectional study of the Beijing Longitudinal Study on Aging II (BLSA II), 4477 subjects (55 years) fulfilled the inclusion criteria. pRBD was determined by the RBD questionnaire Hong Kong (RBDQ-HK). Mini-Mental State Examination (MMSE) and Montreal Cognitive Assessment (MoCA) were used to test the global cognitive performance. Walking speed was used to measure motor function. Logistic regression was performed to assess the relationship between pRBD and cognitive/motor impairments and the moderating effects of education. Results: There were 147 participants (3.3%) with pRBD. Participants with pRBD showed increased risks for cognitive impairment(OR=1.88,95%CI,1.24-2.85, p=0.003), decreased gait speed (OR=1.43, 95% CI, 1.02-2.01, p=0.03), but not for mild cognitive impairment(MCI)(measured by MoCA: OR=1.01,95%CI, 0.68-1.50, p=0.95; measured by MMSE: OR=0.90, 95%CI, 0.59-1.37, p=0.62). Education modified the effect of pRBD on MCI (measured by MoCA: p＜0.001; measured by MMSE: p =0.061) and gait speed (p=0.008). Conclusions: Our findings suggest that pRBD increases the risk of cognitive/motor impairments for a community-dwelling older population and education could alleviate the negative effects. These findings implicate that education may have beneficial effects on delaying the onset of cognitive/motor decline in pRBD subjects.